ANALYSIS OF THE ROLE OF SOCIAL ENTERPRISE STUDIO DAPUR IN POVERTY ALLEVIATION IN TASIKMALAYA REGENCY - Lestari, Mia; Koeswandi, Tika Annisa Lestari; Nurfitriya, Mira (Universitas Pendidikan Indonesia, 2022)
The purpose of this was to analysis of the role of social enterprise studiProsperous living is an ideal condition that is expected by the whole community, so that many efforts are made by the government or the community, one of which is by building social enterprise. Studio Dapur is a social enterprise that has an eco-socialpreneur concept and has a goal to improve the quality of life of people in the surrounding villages. This article will discuss the role of social enterprise that will be carried out by Studio Dapur in alleviating poverty in Tasikmalaya Regency.